Adaptation and energy saving through urban green spaces in Climate Action Plans: the experiences of 20 Global Cities - Ascione, Laura; Gargiulo, Carmela; Guida, Carmen (TeMA - Journal of Land Use, Mobility and Environment, 2025)
Given the rising temperatures and more frequent and intense events typical of the climate crisis, urban areas are increasingly subject to severe effects. In the search for effective adaptation, Climate Action Plans (CAPs) are seen as one of the main strategic approaches, and within these, greening interventions emerge as cross-cutting solutions, achieving goals in both mitigation and adaptation and generating multiple benefits for urban systems. The research reported in the current contribution is part of a broader project aimed at developing a tool in support of decision-making by policy makers for the development of more resilient cities. The present study systematically analyzes the CAPs of a sample of twenty cities recognized globally for their commitment to climate action. The objective is to identify significant relationships between the adaptation strategies put in place by the different cities and their urban, climatic, physical, social, and environmental characteristics, searching in particular to understand the role of green spaces in mitigating the effects of global warming. To achieve this objective, a three-step methodology is proposed. In the first step, multivariate statistical analysis is used to identify clusters of cities based on their climatic, physical, social, and environmental characteristics. In the second step, topic modeling techniques are used in the systematic analysis of the classes of adaptation actions contained in the CAPs. Finally, the results of the first two steps are used to conduct a comparative analysis of cities versus classes of actions, revealing the strengths and weaknesses of the measures in the individual CAPs. This knowledge forms the basis for construction the final tool, aimed at supporting decision-makers in selecting effectively contextualized measures for application in urban scenarios.